Financing growth and development in the Caribbean - the role of the Caribbean Development Bank - Kendall, Patrick...[et al] ([CCMS] [St. Augustine]TT, 2001)
Reviews the role of CDB in the provision of development financing in the region during the period 1970 to 2001.